Dosing and Safety Profile of Aficamten in Symptomatic Obstructive Hypertrophic Cardiomyopathy: Results From SEQUOIA-HCM - Coats, Caroline J; Masri, Ahmad; Nassif, Michael E; Barriales-Villa, Roberto; Arad, Michael; Cardim, Nuno; Choudhury, Lubna; Claggett, Brian; Düngen, Hans-Dirk; Garcia-Pavia, Pablo; Hagège, Albert A; Januzzi, James L; et al. (Journal of the American Heart Association, 2024)
BACKGROUND: Aficamten, a novel cardiac myosin inhibitor, reversibly reduces cardiac hypercontractility in obstructive hypertrophic cardiomyopathy. We present a prespecified analysis of the pharmacokinetics, pharmacodynamics, and safety of aficamten in SEQUOIA-HCM (Safety, Efficacy, and Quantitative Understanding of Obstruction Impact of Aficamten in HCM). METHODS AND RESULTS: A total of 282 patients with obstructive hypertrophic cardiomyopathy were randomized 1:1 to daily aficamten (5-20 mg) or placebo between February 1, 2022, and May 15, 2023. Aficamten dosing targeted the lowest effective dose for achieving site-interpreted Valsalva left ventricular outflow tract gradient <30 mm Hg with left ventricular ejection fraction (LVEF) ≥50%. End points were evaluated during titration (day 1 to week 8), maintenance (weeks 8-24), and washout (weeks 24-28), and included major adverse cardiac events, new-onset atrial fibrillation, implantable cardioverter-defibrillator discharges, LVEF <50%, and treatment-emergent adverse events. At week 8, 3.6%, 12.9%, 35%, and 48.6% of patients achieved 5-, 10-, 15-, and 20-mg doses, respectively. Baseline characteristics were similar across groups. Aficamten concentration increased by dose and remained stable during maintenance. During the treatment period, LVEF decreased by -0.9% (95% CI, -1.3 to -0.6) per 100 ng/mL aficamten exposure. Seven (4.9%) patients taking aficamten underwent per-protocol dose reduction for site-interpreted LVEF <50%. There were no treatment interruptions or heart failure worsening for LVEF <50%. No major adverse cardiovascular events were associated with aficamten, and treatment-emergent adverse events were similar between treatment groups, including atrial fibrillation. CONCLUSIONS: A site-based dosing algorithm targeting the lowest effective aficamten dose reduced left ventricular outflow tract gradient with a favorable safety profile throughout SEQUOIA-HCM. REGISTRATION: URL: https://www.clinicaltrials.gov; Unique Identifier: NCT05186818.
Keywords: tepový objem; Cardiomyopathy, Hypertrophic; benzylaminy; Humans; Stroke Volume; funkce levé komory srdeční; lidé středního věku; Double-Blind Method; Benzylamines; Dose-Response Relationship, Drug; Female; Aged; dospělí; hypertrofická kardiomyopatie; výsledek terapie; senioři; lidé; dvojitá slepá metoda; Atrial Fibrillation; uracil; Adult; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Uracil; vztah mezi dávkou a účinkem léčiva; mužské pohlaví; fibrilace síní; Ventricular Function, Left